Identification of Eleven Novel BRCA Mutations in Tunisia: Impact on the Clinical Management of BRCA Related Cancers - Hamdi, Yosr; Mighri, Najah; Boujemaa, Maroua; Mejri, Nesrine; Ben Nasr, Sonia; Ben Rekaya, Mariem; Messaoud, Olfa; Bouaziz, Hanen; Berrazega, Yosra; Rachdi, Haifa; Jaidane, Olfa; Daoud, Nouha; et al. (Frontiers in Oncology, 2021)
Background Breast cancer is the world's most common cancer among women. It is becoming an increasingly urgent problem in low- and middle-income countries (LMICs) where a large fraction of women is diagnosed with advanced-stage disease and have no access to treatment or basic palliative care. About 5-10% of all breast cancers can be attributed to hereditary genetic components and up to 25% of familial cases are due to mutations in BRCA1/2 genes. Since their discovery in 1994 and 1995, as few as 18 mutations have been identified in BRCA genes in the Tunisian population. The aim of this study is to identify additional BRCA mutations, to estimate their contribution to the hereditary breast and ovarian cancers in Tunisia, and to investigate the clinicopathological signatures associated with BRCA mutations. Methods A total of 354 patients diagnosed with breast and ovarian cancers, including 5 male breast cancer cases, have been investigated for BRCA1/2 mutations using traditional and/or next-generation sequencing technologies. Clinicopathological signatures associated with BRCA mutations have been also investigated. Results 16 distinct mutations were detected: 10 in BRCA1 and 6 in BRCA2, of which 11 are described for the first time in Tunisia including 3 variations that have not been reported previously in public databases namely BRCA1_c.915T>A; BRCA2_c.-227-?_7805+? and BRCA2_c.249delG. Early age at onset, family history of ovarian cancer, and high tumor grade were significantly associated with BRCA status. BRCA1 carriers were more likely to be triple-negative breast cancer compared to BRCA2 carriers. A relatively high frequency of contralateral breast cancer and ovarian cancer occurrence was observed among BRCA carriers and was more frequent in patients carrying BRCA1 mutations. Conclusion Our study provides new insights into breast and ovarian cancer genetic landscape in the under-represented North African populations. The prevalence assessment of novel and recurrent BRCA1/2 pathogenic mutations will enhance the use of personalized treatment and precise screening strategies by both affected and unaffected North African cancer cases.